Classification and grading of the non-invasive urothelial neoplasms: recent advances and controversies. Issue 2 (1st February 2003) - Montironi, R; Lopez-Beltran, A; Mazzucchelli, R; Bostwick, D G
Abstract : The classification and grading of the non-invasive, intraepithelial neoplasms of the urothelium are based on the morphological pattern of growth—that is, papillary or flat (and endophytic)—and on their degree of architectural and cytological abnormalities. Recent advances in the morphological, molecular, and quantitative evaluation of these lesions have contributed to the refinement of the current classification and grading schemes. However, some controversies on the precise criteria and terminology, especially when the papillary lesions are concerned, are still present.